Italian food experiences on Airbnb: A multimodal analysis of hosts’ promotional videos - Irene Cenni; Camilla Vásquez (Ibérica)
To better understand how digital entrepreneurs exploit various communicative modes to appeal to prospective consumers, this study provides a multimodal discourse analysis of videos posted by Airbnb hosts of food-related virtual experiences. Since April 2020 Airbnb has offered a wide range of “Online Experiences” (OEs): OEs are live events facilitated by an Airbnb host via Zoom. Among the most popular OEs are those related to food (i.e., cooking, baking or tasting classes).